Benzene hydrogenation over polydopamine-modified MCM-41 supported Ruthenium-Lanthanum catalyst. Issue 12 (2nd December 2018) - Liao, Hongguang; Xiao, Yanjuan; Yu, Xiaoguang; Liu, Xuanyan; Zhong, Hongmei; Liang, Meidong; He, Haoyan
Abstract: Polydopamine–modified MCM-41 was prepared by sodium periodate–induced polymerization. Ru–La supported on MCM-41 and polydopamine–modified MCM-41 catalysts were prepared by double solvent impregnation method and tested for benzene hydrogenation to cyclohexene. Polydopamine–modified MCM-41 supported Ru–La catalyst exhibits much higher hydrophilicity and more moderate catalytic activity than unmodified MCM-41 supported Ru–La catalyst. The higher hydrophilicity, more moderate catalytic activity, and long-range order of mesoporous structure are beneficial for improving cyclohexene selectivity on account of the promotion of the desorption and the inhibition of the adsorption of cyclohexene. 47.0% of cyclohexene yield was obtained over Ru–La supported on polydopamine–modified MCM-41 in benzene hydrogenation.